Pengaruh Penggunaan Generative AI, Literasi AI, dan Etika Penggunaan AI Terhadap Mahasiswa di Universitas Negeri Semarang - Gilang Ramadhan; Anis Susanti (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
This study examines the influence of Generative AI use, AI literacy, and AI ethics on university students’ critical thinking skills because the rapid adoption of AI in higher education may support learning, but it may also weaken independent reasoning if it is used without adequate understanding and ethical control. The study employed a quantitative associative design with a survey method. Data were collected through a Likert-scale questionnaire from 180 active students in the Office Administration Education Program at Universitas Negeri Semarang and analyzed using instrument testing, classical assumption tests, and multiple linear regression with SPSS 26. The findings show that Generative AI use, AI literacy, and AI ethics each have a positive and significant effect on critical thinking skills, both partially and simultaneously. AI literacy emerged as the most dominant predictor among the three variables. These results indicate that students’ critical thinking is strengthened not only by using AI tools, but also by understanding how AI works and applying responsible academic ethics in their use. However, given the study's cross-sectional design, reliance on self-reported metrics, and narrow focus on a single program at one institution, the generalizability of these outcomes requires cautious interpretation.